Yahoo Web Search

  1. Ad
    related to: K.C
  1. Assuming that k and c are just constants, the equation is separable, divide both ...subject, divide both sides by -1 and raise both sides to the base of e: c - y = e^(-kx) * e^- C As e^- C represents a constant...

    3 Answers · Science & Mathematics · 17/08/2013

  2. f(2) = 2² + k (2) + c = 0 f(-3) = -3² + k (-3) + c = 35 Drop the functions on the left and multiply...4 - 12 + 8 = 0 9 + 18 + 8 = 35 -8 + 8 = 0 27 + 8 = 35 0 = 0 35 = 35 This checks. k = -6 and c = 8

    3 Answers · Science & Mathematics · 15/05/2014

  3. C = k / (m(1 - k )) cross multiply Cm(1 - k ) = k distribute LHS Cm - Cmk = k add Cmk to both sides Cm = k + Cmk factor Cm = k (1 + Cm) divide both sides by (1...

    3 Answers · Science & Mathematics · 26/08/2008

  4. Do you mean y = asin[ k (x - c )] + d? y = asin[ k (x - c )] + d Subtract both sides by d: y...d)/a)/ k Finally, add both sides by c : x = arcsin((y - d)/a)/ k + c I hope this helps!

    1 Answers · Science & Mathematics · 25/02/2011

  5. See binomial equation [1 + x]^n = C (n,0)+ x* C (n,1) +(x^2)* C (n,2)+ (x^3)* C (n,3) ... + [x^n-1...(n,1)+ (2*x)* C (n,2) + (3x^2)* C (n,3)+ ... + (n-1)*[x^n-2]⋅ C (n,n-1) + n*[x^n-1]* C (n,n) put x = 1, you will see that right part is...

    3 Answers · Science & Mathematics · 28/10/2015

  6. ...black is given by the well-known hyper-geometric formula: P( k ) = C [M, k ] * C [(N-M),(n- k )] / C [N,n], /numerator...

    1 Answers · Science & Mathematics · 05/09/2007

  7. ... in the formula: since k = n - (n- k ), we have: C (n, k ) = n! / ( k ! (n- k )! ) C (n, n- k ) = n! / ((n- k )! (n - (n- k ))! = n! / ( (n- k )! k ! )

    1 Answers · Science & Mathematics · 14/03/2012

  8. Since the series includes the term (x- c )^ k we know the power series expresses a function of x "centered at...all over |a_ k (x- c )^ k | is less than 1. So... lim k »∞ | a_( k +1)(x- c )^( k +1) / [a_ k (x- c )^ k ] | < 1 Since (x- c )^( k +1)/(x- c )^ k can...

    1 Answers · Science & Mathematics · 06/12/2012

  9. ...1 Now put x = 1 and you will get ......................n n*(2)^(n - 1) = ∑ k * C (n, k ) ................... k =1

    3 Answers · Science & Mathematics · 24/11/2009

  10. Use the Quotient Rule. = [1-e^(-alpha(u)] [ k +( c )(lamba)] - [ k +( c )(lamda)(u)) (-e^(-alpha(u)) (-alpha)] / (1-e^(-alpha)(u)]^2 Note...

    1 Answers · Science & Mathematics · 27/03/2008

  1. Ads
    related to: K.C
  1. Try asking your question on Yahoo Answers